Conceptuals Maps vs Summaries: Differences in the Modalities of Collaborative Construction - Roselli, Nestor Daniel (2020)
Two teaching resources are compared: the conceptual map and the summary, understood as external systems of cognitive representation. In the theoretical approach used, such external systems are not understood as mere outsourcing of thought, but, conversely, as types of representational activity that format the cognition itself. In this sense, maps and summaries would have different cognitive effects. But this research goes further: such differential effects would also be psychosocial, formating sociocognitive interaction when the activity is carried out in a collaborative way. The experimental design compares four conditions from two identical subsamples, in which both the task that 18 dyads of university students must perform (map and summary) and the two source-texts used are balanced. The analysis compares the individual productions with the collective of each dyad, focusing on the modalities of collective construction based on the individual productions. Thus, three basic modalities are distinguished: homogeneous, symmetrical heterogeneous and asymmetrical heterogeneous. The analysis differentiates between cognitive or content aspects, and specifically formal aspects. Descriptively, data shows a tendency in the sense of the hypothesis raised, showing that both external systems shape differently the sociocognitive interaction.